Anxel Beam Shrinkage Method and Heterogeneous Computing-Accelerated Full-Image Theory Method Ray Tracing Enabling Massive Outdoor Propagation Modeling - Kim, Yongwan; Yang, Hyunjun; Kim, Hooyoung; Jo, Junpyo; Oh, Jungsuek (IEEE transactions on antennas and propagation, 2024)
Despite their accuracy, traditional image theory (IT) ray tracers were previously limited to basic simulation environments with fewer field observation points (FOPs) and lower ray bounce orders due to computational inefficiencies. In this study, we propose a novel full-3-D anxel beam shrinkage (ABS) method and heterogeneous computing-accelerated full-IT method ray-tracing (RT) framework enabling massive outdoor propagation modeling. The proposed framework is divided into three components: 1) visibility preprocessing; 2) visibility tree generation, which introduces a novel ABS method to expedite the creation process and minimize the visibility tree's size; and 3) shadow testing and field calculation, incorporating a heterogeneous computing algorithm designed to efficiently manage numerous FOPs. We also demonstrated that the proposed framework, utilizing both central processing unit (CPU) and graphical processing unit (GPU) parallel computing, is 651 times faster than the IT method solver of WinProp, which supports only CPU parallel computing. Furthermore, it is confirmed that the proposed RT framework can handle 1× 1 km wide and dense urban outdoor simulation with up to the maximum ray bouncing order of 6 and thousands of FOPs. The proposed RT framework could serve as a foundation for future advancements in IT method RT techniques in complex and massive scenarios, which were previously exclusive to the shooting and bouncing rays method ray tracers.